Halal & Safe Food : Edukasi Gaya Hidup Halal (Sebuah Analisis Resepsi Khalayak) - mauri, tantya safa (AL MUNIR : Jurnal Komunikasi dan Penyiaran Islam, 2023)
AAs a country with a Muslim majority,Indonesian people still do not understand the implementation of a halal lifestyle. Halal lifestyle education through the media is a new breakthrough in increasing understanding of halal concepts. This research aims to analyze the audience's reception of Halal Safe Food content as a model of a halal lifestyle. This research uses a qualitative research method with the Reception Analysis approach of Stuart Hall's Encoding - Decoding Theory. On the encoding side, researchers analyzed the knowledge framework conveyed by Leli Azizah via Tiktok social media. Meanwhile, on the decoding side, researchers looked at the knowledge framework of 6 informants who watched video content discussing Angciu. The data collection technique is carried out by observation or video observation. In the next phase, researchers looked at the synchronization of encoding and decoding by describing the reception process. The results of this research show that on the encoding side of the first preparation function, namely the media agenda, Leli Azizah is still not a role model in halal lifestyle guidelines. Second, the community agenda shows that the community has accepted the agenda presented by Leli Azizah regarding a halal lifestyle. Third, there is still no synchronization of the policy agenda between the media agenda and society. On the Decoding side, three people are in the Hegemonic Dominant position, namely the position that the public fully agrees about Angciu that it is haram. The other three people are in the Negotiated position, nam